Implementasi Strategi Two Stays Two Strays Untuk Meningkatkan Kemampuan Literasi Mapel Ekonomi Peserta Didik Kelas X-10 MAN 1 Pasuruan - Masruroh, Nafisatul (Balai Diklat Keagamaan Surabaya, 2023)
In response to the results of the Program for International Student Assessment (PISA) survey released by the Organization for Economic Co-operation and Development (OECD) in 2019, that Indonesia ranks 62nd out of the 70 lowest countries with low literacy levels, the government is very concerned about launching the School Literacy Movement (GLS). This Classroom Action Research (CAR) was carried out as an effort to improve the literacy skills of students in class X-10 MAN 1 Pasuruan in the even semester of the 2022-2023 school year. The formulation of the problem is (1) how is the implementation of the Two Stays Two Strays (TSTS) strategy to increase the literacy skills of Business Entities in the Economy subject at class X-10 MAN 1 Pasuruan? and (2) to what extent can the TSTS strategy increase the literacy skills of Business Entities in the Economy subject at class X-10 MAN 1 Pasuruan? Based on the results of the implementation of cycle 1 and cycle 2, the researcher concluded; first, the implementation of the TSTS strategy in class X-10 MAN 1 Pasuruan can be fully (100%) implemented according to the guidelines in the literature review. Second, the implementation of the TSTS strategy can significantly improve the literacy skills of students in class X-10 MAN 1 Pasuruan both in cognitive and psychomotor aspects. In the cognitive aspect there was a very significant increase from cycle 1 to cycle 2. The same thing also happened in the psychomotor aspect. Thus, the second and third indicators of success where the mean score of X-10 class on the cognitive and psychomotor aspects of > 80% is well fulfilled. Suggestions for further research, first, the TSTS strategy is very appropriate to choose in the teaching and learning process of economics and other subjects that have a large amount of material, because this strategy is able to improve students' literacy skills so that they master the subject well. Second, for future researchers it is recommended to combine it with other strategies in order to obtain a more optimal increase in literacy.